Life in the Exoplanet K2‑18b? - de Freitas Pacheco, José Antonio (Earth and Planetary Science, 2025)
The possible presence of dimethyl sulfide (DMS) in the atmosphere of the exoplanet K2‑18b—an ocean‑bearing Hycean world candidate—has intensified the interest in its potential habitability. This sulfur compound, primarily produced by marine life on Earth, is considered a potential biosignature. We investigate whether the observed atmospheric DMS levels could plausibly originate from biological activity, assuming Earth‑like metabolic pathways. Through energy budget modeling, this study estimates the DMS production capacity of a hypothetical biosphere on K2‑18b and finding that, even under optimistic assumptions, biogenic DMS levels would fall several orders of magnitude short of those inferred from James Webb Space Telescope (JWST) observations. Additionally, we examine DMS atmospheric lifetimes under K2‑18b’s environmental conditions. The results suggest that, while the presence of DMS cannot be conclusively attributed to biological activity, its detection remains inconclusive as a biosignature due to possible non‑biological production mechanisms and uncertainties in spectral retrieval procedures. We conclude that current evidence does not support the presence of life on K2‑18b and emphasize the need for more refined observational data and atmospheric models. ER